AB0628 The direct and indirect costs of an osteoporotic fracture: a prospective evaluation of elderly patients with a clinical fracture. (23rd January 2014) - Eekman, D.; ter Wee, M.; Coupé, V.; Erisek-Demirtas, S.; Kramer, M.; Lems, W.
Abstract : Background: Osteoporotic fractures have large economic consequences for the health care system and for society. Most available data concerns direct medical costs only. Objectives: The aim of this study was to gain insight into all the current overall costs (direct medical, direct non-medical and indirect costs) of clinical fractures in osteoporotic patients aged 50 years and older in the Netherlands. Methods: The aim of this study was to gain insight into all the current overall costs (direct medical, direct non-medical and indirect costs) of clinical fractures in osteoporotic patients aged 50 years and older in the Netherlands. Results: 116 patients were included, of these patients, 69 completed all four diaries, 34 patients returned two diaries or more. Humerus fractures were most expensive with total one year costs of €16.817 (95% CI €10.040 - €29.969) per patient. The second most expensive fractures were clinical spine fractures with total costs of €14.036 (95% CI €1.888 - €25.782) per patient. Direct medical costs were highest for hip fractures (€9.917, 95% CI €8.478 - €13.614). However, the sample size for this estimate was small (4 patients) and confidence intervals were wide. Direct medical costs were very low for patients with clinical spine fractures (€677, 95% CI €438 - €963 per patient). Although spinal fractures have low direct medical and non-medical costs, indirect costs in this group were highest (€12.521, 95% CI €5.971 - €19.651 per patient), accounting for 89% of the total costs for this fracture. For all other fractures indirect costs account for roughly half of the total costs. Cost estimates in the sensitivity analyses were similar or lower than the estimates for the complete cases. Conclusions: Indirect medical costs account for roughly half of the total costs of clinical fractures in patients 50 years and over. When considering fracture related costs from a societal perspective, it is very important to take these costs into account. Disclosure of Interest: None Declared